Glucocorticoid receptor in prostate epithelia is not required for corticosteroid‐induced epithelial hyperproliferation in the mouse prostate. Issue 10 (23rd May 2014) - Zhao, Bin; Choi, Jaesung (Peter); Jaehne, Maria; Gao, Yan Ru (Ellen); Desai, Reena; Tuckermann, Jan; Zhou, Hong; Handelsman, David J.; Simanainen, Ulla
<x xml:space="preserve">Abstract</x> BACKGROUND Glucocorticoids are used as a last resort treatment for prostate cancer but the cell‐specific glucocorticoid receptor (GR) mediated actions and the role of endogenous glucocorticoids in prostate are not understood. METHODS We evaluated the influence of prostate epithelial GR mediated actions of glucocorticoids in prostate structural development by comparing the intact wild‐type (WT) and prostate epithelia selective GR knockout (peGRKO) males at 8, 20, and 35 weeks of age. We also determined the cell‐specific role of GR on corticosterone treatment induced prostate abnormalities by treating peGRKO and WT male mice with corticosterone depot pellets or placebo for 4 weeks. RESULTS GR was not expressed in the epithelial cells of peGRKO prostate unlike WT but was expressed in stromal of both peGRKO and WT mice. Nevertheless, prostate weights, histological appearance, and secretory protein probasin expression in peGRKO were no different from WT. Despite lacking epithelial GR, the peGRKO prostate demonstrated corticosterone treatment induced hyperplasia similar to WT suggesting that stromal rather than epithelial GR mediates the hyperproliferative mouse prostate response to corticosterone. As circulating androgen levels were not affected by corticosterone treatment, this effect is likely to be mediated directly via prostate GR. CONCLUSIONS Sustained administration of corticosterone induces prostate hyperplasia, which is mediated via GR expressed predominantly in the stroma. Thus GR mediated actions in the prostate may have significant cell‐specific effects that could be utilized for more rational therapeutic approaches in prostate cancer treatment. This also illustrates the paracrine hormonal mechanisms in prostate pathophysiology. Prostate 74:1068–1078, 2014. © 2014 Wiley Periodicals, Inc.